THE LONG-RUN PERFORMANCE OF GREEK INITIAL PUBLIC OFFERINGS - Glezakos, Michael; Gotzageorgis, George (Journal of European Economy, 2018)
This article examines the long run performance of initial public offerings (IPO’s) in Greece, over the seven-year period of 1994-2000. After analyzing a sample of 176 IPO’s, it was concluded that IPO’s tend to outperform the market by 10,84% of cumulative market-adjusted return over the first three years from the listing day. The results are contradictory to empirical findings for many other developed markets. However, they are explained by such variables as initial returns, issue size and period and price volatility. Moreover, it was depicted that the «fads» hypothesis as well as the «windows of opportunity» and the «uncertainty and divergence of opinion» hypotheses can explain the long-term performance of the IPO’s listed at the Athens Stock Exchange.